Influence of the cleaning method employed prior to the use of ionomeric materials in micro filtration of cavities at the cervical level - Muñoz Estrella, María (2019)
Objective: To evaluate the influence of the cleaning of the cavity with aluminum oxide and pumice on the marginal microfiltration when using ionomeric materials (IV). Materials and Methods: In 40 human premolar teeth, cavities were prepared at the level of the cemetery amelo, the teeth were randomly divided into 4 groups (n: 10) received cleaning and restoration procedures according to the group, G1 cleaning with abrasive air and restoration with IV Ketac Molar Easy Mix (IVKM), G2 abrasive air and restoration with IV Gold Label 2 (IVGL), G3 pumice stone and IVKM, G4 pumice stone and IVGL. After the process of thermal aging, pigmentation with methylene blue and cutting in the lingual buccal direction, the fragments with the highest integrity were analyzed to the stereomicroscope by three evaluators who established the degree of micro filtration at the cervical and occlusal levels; the average obtained by surface per tooth was analyzed statistically. Results: The analysis performed revealed normality in the data, finding through the Tukey test that all groups are equal, with no difference in treatment and material used. Conclusions: Micro filtration was evident in all the groups independent of the cleaning treatment and the restoration material used, most notably at the level of the cervical wall.